Broken Bengal: Tropes of Conviviality and Fracture in Bangla Fiction - O'Connor, Maurice (Archīum Ateneo, 2024)
This essay examines how Bangla fiction employs the trope of conviviality as a means to provide an affective understanding of the partition of Bengal. Of principal concern is how Bengali writers, regardless of their religious affiliation, insist upon the existence of a common Bengali across the religious divide. I open my essay with a brief historiographic introduction to the fracturing of Bengali society, contextualizing the backstories that are rarely fleshed out within Bangla fiction yet are elliptically present. Conviviality is the term I use to frame a common Bangla culture, and I explore the concept through Ivan Illich, Thomas Erikson and Tina Steiner. While conviviality is, moreover, applied to modern multicultural societies, I argue that it is also a valid concept for the plural society of pre-partition Bengal. I shall examine the dramatic structures employed which aid in the discovery of new perspectives on the societal fracture that occurred during the partition of Bengal. A phenomenological approach, I argue, is often used to represent this fracture. Bangla fiction seeks to represent the structures of experience as presented to an individual rather than being reflecting prior truths as presented through history. This concept is explained through Maurice Merleau-Ponty’s understanding of the phenomenological world. I shall also draw attention to texts that narrate the existence of cross-class solidarity. By focusing on class instead of religion, I identify an alternative way to configure the trope of conviviality within Bangla literature. Finally, I examine how literature explores the loss of this syncretic Bengali culture through the specific trope of nostalgia. Here, I employ Svetlana Boym’s understanding of the term and her distinction between reflective and restorative types. Regarding the former, reflective nostalgia acknowledges the imperfect process of remembrance, and I argue that Bangla literature employs this form of nostalgia, mediated through what Boym defines as “individual and cultural memory” (49).